2011
DOI: 10.1103/physrevc.83.054618
|View full text |Cite
|
Sign up to set email alerts
|

First superheavy element experiments at the GSI recoil separator TASCA: The production and decay of element 114 in thePu244(Ca

Abstract: Experiments with the new recoil separator, TASCA, at the GSI were performed using beams of 48 Ca to irradiate targets of [206][207][208] Pb leading to the production of [252][253][254]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 51 publications
8
78
0
Order By: Relevance
“…As a first step towards a chemistry experiment with element 114 at TASCA, production and decay of element 114 in the 244 Pu( 48 Ca, 3 − 4n) 288,289 114 reaction was studied [50,51]. The obtained results confirmed the nuclear properties as reported from experiments at the DGFRS [74], and the experiment also verified the superior performance of TASCA for the subsequent chemical study of element 114.…”
Section: Gas Phase Chemical Studies Of Element 114supporting
confidence: 69%
See 1 more Smart Citation
“…As a first step towards a chemistry experiment with element 114 at TASCA, production and decay of element 114 in the 244 Pu( 48 Ca, 3 − 4n) 288,289 114 reaction was studied [50,51]. The obtained results confirmed the nuclear properties as reported from experiments at the DGFRS [74], and the experiment also verified the superior performance of TASCA for the subsequent chemical study of element 114.…”
Section: Gas Phase Chemical Studies Of Element 114supporting
confidence: 69%
“…The solid angle is 13.3 msr [49], which is significantly larger than, e.g., the 10 msr of the Dubna Gas-Filled Recoil Separator (DGFRS). The efficiency of TASCA for actinide-target based 48 Cainduced fusion reactions [50,51] is roughly 50% larger than that of the DGFRS and approaches the best values reported from the BGS [52]. TASCA thus combines the advantages of these two separators, i.e., the large transmission of the BGS and the small dispersion of the DGFRS.…”
Section: Formation Of the Community Building And Commissioning Of Tascamentioning
confidence: 91%
“…It confirmed the synthesis of the two most neutron-rich isotopes of element 114, 0.69-s 288 114 and 2.1-s 289 114 [37]. Moreover, it showed that these two isotopes are produced with a cross section of the order of 10 pb [38] -the highest cross section observed in 48 Ca induced production of transactinides. These nuclei have longer half-lives and are produced with much higher cross sections than the ones in cold fusion reactions, thus providing great perspectives for chemical studies.…”
Section: Introduction and Historical Remarkssupporting
confidence: 62%
“…Both lead to stable operation at beam currents of often more than 1 µA (particle). Separator efficiencies of about 60% for element 114 produced in the 48 Ca on 244 Pu reaction at TASCA [130] and still 13% for 265 Sg synthesized in the very asymmetric 22 Ne on 248 Cm reaction at GARIS [79] have been reached.…”
Section: Physical Pre-separatorsmentioning
confidence: 87%
See 1 more Smart Citation